Progress of research on molecular targeted therapies for colorectal cancer - Huang, Shilin; Ye, Jiazhou; Gao, Xing; Huang, Xi; Huang, Julu; Lu, Lu; Lu, Cheng; Li, Yongqiang; Luo, Min; Xie, Mingzhi; Lin, Yan; Liang, Rong (Frontiers in Pharmacology, 2023)
Colorectal cancer (CRC) is one of the most common malignancies, accounting for approximately 10% of global cancer incidence and mortality. Approximately 20% of patients with CRC present metastatic disease (mCRC) at the time of diagnosis. Moreover, up to 50% of patients with localized disease eventually metastasize. mCRC encompasses a complex cascade of reactions involving multiple factors and processes, leading to a diverse array of molecular mechanisms. Improved comprehension of the pathways underlying cancer cell development and proliferation, coupled with the accessibility of relevant targeted agents, has propelled advancements in CRC treatment, ultimately leading to enhanced survival rates. Mutations in various pathways and location of the primary tumor in CRC influences the efficacy of targeted agents. This review summarizes available targeted agents for different CRC pathways, with a focus on recent advances in anti-angiogenic and anti-epidermal growth factor receptor agents, BRAF mutations, and human epidermal growth factor receptor 2-associated targeted agents.